Quality appraisal of clinical practice guidelines for the management of Dysphagia after acute stroke - Gao, Shi-Lin; Liu, Chang-Qing; Han, Qing-Hua; Dai, Xiao-Rong; Liu, Yi-Wen; Li, Ka (Frontiers in Neurology, 2023)
Objectives Dysphagia is a common complication in stroke patients, widely affecting recovery and quality of life after stroke. The objective of this systematic review is to identify the gaps that between evidence and practice by critically assessing the quality of clinical practice guidelines (CPGs) for management of dysphagia in stroke. Methods We systematically searched academic databases and guideline repositories between January 1, 2014, and August 1, 2023. The Appraisal of Guidelines for Research and Evaluation (AGREE II) instrument was used by two authors to independently assess CPG quality. Results In a total of 14 CPGs included, we identified that three CPGs obtained a final evaluation of “high quality,” nine CPGs achieved “moderate quality” and two CPGs received “low quality.” The domain of “scope and purpose” achieved the highest mean score (91.1%) and the highest median (IQR) of 91.7% (86.1, 94.4%), while the domain of “applicability” received the lowest mean score (55.8%) and the lowest median (IQR) of 55.4% (43.2, 75.5%). Conclusion The CPG development group should pay more attention to improving the methodological quality according to the AGREE II instrument, especially in the domain of “applicability” and “stakeholder involvement;” and each item should be refined as much as possible.